Politics of Law of Social Security of Passenger Accidents Construction of State Responsibility - Maryanto Maryanto; Ahmad Suhasan (Law Development Journal, 2021)
The role of the presence of the state is important so that the implementation of social security from the government to the community is managed from compulsory contributions and community contributions. Management and control of the funds are submitted to the State Owned Enterprises (BUMN) PT. Jasa Raharja. This research method is normative juridical (normative law research) using normative legal studies in the form of legal behavior products. Research findings: (1) The Political Law of Social Security for Passenger Accidents and Road Traffic Accidents provides an overview of the Insurance business that has been managed so far PT. Jasa Raharja is a social insurance program that can be organized by BUMN, so PT. Jasa Raharja as a state-owned company is the only provider of social security insurance for passenger accidents and road traffic accidents. (2) Barriers to adjusting the implementation of the Social Security Program based on Act No. 40 of 2014 concerning Insurance in terms of regulation between Act No. 33 and 34 of 1964 with Act No. 40 of 2014 concerning Insurance, the institutional provisions of article 89 of the Insurance Law are implemented, so there is a fundamental change in the administration of the mandatory insurance coverage for passenger accidents and road traffic accidents.